1994
DOI: 10.1073/pnas.91.20.9387
|View full text |Cite
|
Sign up to set email alerts
|

Brain neurons and glial cells express Neu differentiation factor/heregulin: a survival factor for astrocytes.

Abstract: Neu differentiation factor (NDF, also cafled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
1
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 22 publications
8
94
1
1
Order By: Relevance
“…The results of this analysis indicated that ligand expression dramatically decreased with age, whereas a parallel increase in erbB-3 expression and a concomitant moderate down-regulation of erbB-4, occurred in the ®rst 3 weeks of postnatal life ( Figure 4). This observation is consistent with the lack of signi®cant erbB-3 expression in E10.5 mouse embryos (data not shown) and the results of immunohistochemical (Pinkas-Kramarski et al, 1994), as well as in situ hybridization analyses (Chen et al, 1994) of neuregulin, whose neural expression appears to decrease, but not disappear, after birth. Possibly, ErbB-4 is the NDF receptor that mediates the major cerebellar neurogenic phase in the ®rst week of postnatal life, but ErbB-3 replaces it, at least in part, in later stages and in adult life.…”
Section: Expression Of Ndf Receptors In Adult Brain and In The Develosupporting
confidence: 90%
See 4 more Smart Citations
“…The results of this analysis indicated that ligand expression dramatically decreased with age, whereas a parallel increase in erbB-3 expression and a concomitant moderate down-regulation of erbB-4, occurred in the ®rst 3 weeks of postnatal life ( Figure 4). This observation is consistent with the lack of signi®cant erbB-3 expression in E10.5 mouse embryos (data not shown) and the results of immunohistochemical (Pinkas-Kramarski et al, 1994), as well as in situ hybridization analyses (Chen et al, 1994) of neuregulin, whose neural expression appears to decrease, but not disappear, after birth. Possibly, ErbB-4 is the NDF receptor that mediates the major cerebellar neurogenic phase in the ®rst week of postnatal life, but ErbB-3 replaces it, at least in part, in later stages and in adult life.…”
Section: Expression Of Ndf Receptors In Adult Brain and In The Develosupporting
confidence: 90%
“…Similar to the expression pattern of NDF/neuregulin in adult rat brain (Chen et al, 1994;Pinkas-Kramarski et al, 1994), both receptors were expressed in regions of the limbic and the motor systems. These include various sites in the cerebral cortex (e.g.…”
Section: Expression Of Ndf Receptors In Adult Brain and In The Develosupporting
confidence: 52%
See 3 more Smart Citations